Balanced stress fracturing theory and its application in platform well fracturing during unconventional oil and gas development. (November 2022) - Meng, Hu; Wang, Xiaoqiong; Ge, Hongkui; Chen, Lu; Yao, Yuan; Shen, Yinghao; Zhang, Zuodong
Abstract: Platform well fracturing is essential for the efficient development of unconventional oil and gas (UOG), and it has been widely applied in oilfields. Field practices have revealed that various fracturing methods result in different stimulation performances, but the mechanisms responsible for these differences are not completely understood. To explore the characteristics of the inter-well stress interference of various platform well fracturing methods, a numerical model was established for the systematic assessment of the stress field of simultaneous fracturing, zipper fracturing (ZF), modified zipper fracturing, and synergic fracturing (SF). Based on these analyses, balanced stress fracturing (BSF) has been proposed to significantly reduce the horizontal stress difference. This study indicates that the fracturing methods significantly impact the evolution of induced stress, and that ZF and SF can achieve a balanced stress field and the utilization of an inter-well reservoir through a reasonable fracture distribution mode and fracturing operation. Combined with the interlaced fracture distribution mode, interactive fracturing, and overall front parallel fracturing, BSF can improve the fracture network complexity (FNC) and reduce the risk of casing deformation. Moreover, BSF helps achieve higher production and a more uniform stress field in platform well fracturing. This study presents an effective measure to increase FNC and reduce the occurrence of casing deformation during UOG development.